Biodegradable film material as well as preparation method and application thereof

By combining PBAT resin with PLA resin with specific D-lactic acid content, calcium carbonate, inorganic opening additives and organic opening additives, a biodegradable membrane material was prepared, which solved the problem of the inability to increase the production capacity of the degradable biofilm material during high-speed blowing of the film and the adhesion of the membrane bag in the prior art, and achieved high productivity and good opening performance.

CN119875324APending Publication Date: 2025-04-25KINGFA SCI & TECH CO LTD

Patent Information

Application Number
CN202510119978.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The production capacity of existing biodegradable biofilm materials cannot be increased when blown at high speed, and the membrane bags are prone to sticking when coiled and cannot be opened normally.

Method used

A biodegradable membrane material is prepared by combining PBAT resin with a specific D-lactic acid content, a specific particle size of calcium carbonate, an inorganic opening additive of a specific particle size and an organic opening additive. The material is melt-extruded under conditions of 160-200°C by a twin screw extruder.

Benefits of technology

The high productivity of biodegradable membrane materials when blowing film at high speed is achieved, while also having good opening performance, high up token value and excellent dart impact performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005258664920000051
    Figure BDA0005258664920000051
  • Figure BDA0005258664920000061
    Figure BDA0005258664920000061
  • Figure BDA0005258664920000062
    Figure BDA0005258664920000062
Patent Text Reader

Abstract

The invention relates to a biodegradable film material as well as a preparation method and application thereof, and belongs to the technical field of compositions of high-molecular compounds. The biodegradable film material is prepared from the following components in parts by weight: 39 to 85.6 parts of PBAT resin, 2 to 10 parts of PLA resin, 10 to 40 parts of calcium carbonate, 2 to 10 parts of an inorganic opening auxiliary agent and 0.2 to 1 part of an organic opening auxiliary agent, the molar content of D-lactic acid in the PLA resin is less than or equal to 6%; the particle size D50 of the calcium carbonate is 1.5-2.5 [mu] m; the particle size D50 of the inorganic anti-blocking agent is 1-5 [mu] m. The biodegradable film material not only can be used for high-speed film blowing, but also has good opening performance, high factor value and excellent falling dart impact performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer compound compositions, and in particular to a biodegradable film material and a preparation method and application thereof. Background Art

[0002] Compared with traditional non-degradable PE-type film materials, current degradable biofilm materials can only be used under low-speed film blowing (≤40kg / h), which is far lower than the production capacity of PE-type film materials to achieve the same bag type (film blowing speed ≥80kg / h). The main reason why the production capacity of degradable biofilms cannot be improved is that the molecular structure and melt strength of degradable biofilm materials are significantly different from those of PE-type film materials, which leads to the inability to increase production capacity. In addition, since flexible biodegradable polyesters (such as PBAT) are mostly semi-crystalline materials, the film surface itself cools down slowly. After the film blowing speed is increased, the time taken for the film surface to go from film output to winding is shorter. However, the shortened cooling time causes the film surface temperature to remain high during winding. Under high temperature, the film bag is subjected to the winding pressure and sticks together, which is specifically manifested as the inability to open the film bag normally after cutting the bag. To address this issue, although the opening properties of the film bag can be improved by adding inorganic or organic opening agents, inorganic opening agents mainly improve the opening performance by increasing the roughness of the film bag surface, which will affect the texture of the film bag and even the mechanical properties of the film bag; while organic opening agents will cause the dyne value of the film bag surface to decrease, making it difficult to meet the printing requirements of the film bag. Summary of the invention

[0003] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a biodegradable film material and a preparation method and application thereof.

[0004] To achieve the above object, the technical solution adopted by the present invention is:

[0005] In a first aspect, the present invention provides a biodegradable film material, comprising the following components by weight: 39 to 85.6 parts of PBAT resin, 2 to 10 parts of PLA resin, 10 to 40 parts of calcium carbonate, 2 to 10 parts of inorganic opening aid, and 0.2 to 1 part of organic opening aid;

[0006] The molar content of D-lactic acid in the PLA resin is ≤6%;

[0007] The particle size D of the calcium carbonate 50 1.5~2.5μm;

[0008] The particle size D of the inorganic opening agent 50 1~5μm.

[0009] The present invention combines PBAT resin with PLA resin having a specific D-lactic acid content, calcium carbonate having a specific particle size, an inorganic opening aid having a specific particle size, and an organic opening aid, so that the biodegradable film material can not only be used for high-speed film blowing, but also has good opening performance, high Gondine value, and excellent dart impact performance.

[0010] The mass percentage of PBAT resin in the above-mentioned biodegradable film material is ≥35%; optionally, the weight percentage of PBAT resin in the biodegradable film material can be 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, and 85 parts; the weight percentage of PLA resin can be 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, and 10 parts; the weight percentage of calcium carbonate can be 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, and 40 parts; the weight percentage of inorganic opening aid can be 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, and 10 parts; the weight percentage of organic opening aid can be 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, and 1 part.

[0011] The molar content of D-lactic acid in the above PLA resin can specifically be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, and 5%. The molar content of D-lactic acid in the PLA resin can be obtained by the peak area of ​​D-methyl lactate / (peak area of ​​L-methyl lactate+peak area of ​​D-methyl lactate). The specific testing method can refer to CN115403902A.

[0012] As a preferred embodiment of the biodegradable film material of the present invention, the PBAT resin in the biodegradable film material is 50 to 66.5 parts by weight, the PLA resin is 4 to 8 parts by weight, the calcium carbonate is 25 to 35 parts by weight, and the inorganic opening aid is 4 to 6.5 parts by weight.

[0013] As a preferred embodiment of the biodegradable film material of the present invention, based on the total molar amount of terephthalic acid monomer units and adipic acid monomer units in the PBAT resin, the molar ratio of the terephthalic acid monomer units is 46% to 50%; the number average molecular weight of the PBAT resin is 60,000 to 80,000 g / mol, and the molecular weight distribution coefficient is 1.6 to 1.7.

[0014] Preferably, based on the total molar amount of the terephthalic acid monomer unit and the adipic acid monomer unit in the PBAT resin, the molar ratio of the terephthalic acid monomer unit is 47% to 49%.

[0015] Optionally, the number average molecular weight of the PBAT resin may be any one of 60,000 g / mol, 62,000 g / mol, 64,000 g / mol, 66,000 g / mol, 68,000 g / mol, 70,000 g / mol, 72,000 g / mol, 74,000 g / mol, 76,000 g / mol, 78,000 g / mol, and 80,000 g / mol, or any two of the range values; the molecular weight distribution coefficient may be any one of 1.6, 1.62, 1.64, 1.66, 1.68, and 17, or any two of the range values.

[0016] The number average molecular weight (Mn) and weight average molecular weight (Mw) of the PBAT resin can be measured by GPC using Waters ACQUITY APC TM The equipment was tested at a test temperature of 40°C, using XT45, XT200 and XT459 chromatographic columns, tetrahydrofuran as the solvent, a mobile phase flow rate of 0.5 mL / min, and polystyrene standards as the standard sample. The results were averaged three times.

[0017] As a preferred embodiment of the biodegradable film material of the present invention, the number average molecular weight of the PBAT resin is 65000-75000 g / mol.

[0018] As a preferred embodiment of the biodegradable film material of the present invention, the molecular weight distribution coefficient of the PBAT resin is 1.62 to 1.68.

[0019] As a preferred embodiment of the biodegradable film material of the present invention, the molar content of D-lactic acid in the PLA resin is 1% to 5%.

[0020] As a preferred embodiment of the biodegradable film material of the present invention, the inorganic opening aid includes at least one of talc, montmorillonite and mica.

[0021] As a preferred embodiment of the biodegradable film material described in the present invention, the organic opening aid includes at least one of erucamide, oleamide, monoglycoside ester, N,N'-ethylene bisstearamide, Fischer-Lehr wax, pentaerythritol stearate, fatty acid amide, and stearic acid; further preferably, it is at least one of oleamide, monoglycoside ester, and N,N'-ethylene bisstearamide.

[0022] In a second aspect, the present invention provides a method for preparing the above-mentioned biodegradable film material, comprising the following steps: mixing the components uniformly and then melt-extruding to obtain the biodegradable film material.

[0023] Optionally, in the above preparation method, a twin-screw extruder may be used for melt extrusion, the melt extrusion temperature is 160-200° C., and the screw speed of the twin-screw extruder is 250-350 rpm.

[0024] In a third aspect, the present invention provides use of the above-mentioned biodegradable film material in preparing a biodegradable film bag.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention combines a specific PBAT resin with a PLA resin having a specific D-lactic acid content, calcium carbonate having a specific particle size, an inorganic opening aid having a specific particle size, and an organic opening aid, so that the biodegradable film material can not only be used for high-speed film blowing, but also has good opening performance, high Gondine value, and excellent dart impact performance. DETAILED DESCRIPTION

[0027] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0028] Unless otherwise specified, other materials, reagents, etc. used in the examples and comparative examples can be obtained from commercial sources.

[0029] 1. Raw materials and reagents

[0030] 1) PBAT resin

[0031] The PBAT resin is prepared by the following preparation method: terephthalic acid, adipic acid, 1,4-butanediol (excess), and a branching agent (500 ppm) are added to a reactor, stirred at 190° C. for T1 (1 to 8 hours), and then tetrabutyl titanate is added as a catalyst, and the temperature is raised to 240° C. for reaction for T2 (3 to 20 hours), thereby obtaining different PBAT resins; wherein the molar ratio of the total amount of terephthalic acid and adipic acid to 1,4-butanediol is 1:1.4;

[0032] The T content (based on the total molar amount of terephthalic acid monomer units and adipic acid monomer units, wherein the proportion of terephthalic acid monomer units) is achieved by keeping the total amount of terephthalic acid and adipic acid unchanged and adjusting the molar proportion of terephthalic acid. The number average molecular weight and molecular weight distribution coefficient are achieved by adjusting the reaction times T1 and T2, as shown in Table 1.

[0033] Table 1 PBAT resin 1~10

[0034] PBAT resin Number average molecular weight Molecular weight distribution coefficient T content PBAT resin 1 71590g / mol 1.59 48 mol% PBAT resin 2 69210g / mol 1.62 48 mol% PBAT resin 3 68510g / mol 1.68 48 mol% PBAT resin 4 67860g / mol 1.63 46 mol% PBAT resin 5 69569g / mol 1.64 50mol% PBAT resin 6 69130g / mol 1.71 48 mol% PBAT resin 7 70450g / mol 1.66 51 mol% PBAT resin 8 67680g / mol 1.65 45mol% PBAT resin 9 56690g / mol 1.66 48 mol% PBAT resin 10 83220g / mol 1.65 48 mol%

[0035] 2) PLA resin

[0036] PLA resin 1, molar content of D-lactic acid is 4%, manufacturer: Jinfa Biotechnology, brand: KB600 NF30;

[0037] PLA resin 2, molar content of D-lactic acid <1%, manufacturer: Jinfa Biotechnology, brand KB600 NF10;

[0038] PLA resin 3, the molar content of D-lactic acid is 10%, the manufacturer is Jinfa Biotechnology, the brand is KB600 NF50.

[0039] 3) Calcium carbonate

[0040] Calcium carbonate 1, particle size D 50 1.5μm, manufacturer Guangdong Xinrong, brand ACC-815;

[0041] Calcium carbonate 2, particle size D 50 2μm, manufacturer: Switzerland Omya, brand: Omyacarb 1T-CU;

[0042] Calcium carbonate 3, particle size D 50 1.2μm, manufacturer Guangdong Xinrong, brand ACC-812;

[0043] Calcium carbonate 4, particle size D 50 5μm, manufacturer: Switzerland Omya, brand: Omyacarb 5T-JI.

[0044] 4) Inorganic opening aids

[0045] Talc 1, particle size D 50 4.5μm, manufacturer Liaoning Xinda, brand SDC-F7;

[0046] Talc 2, particle size D 50 0.7μm, manufacturer Liaoning Aihaiyimi, brand HTPultra5 L;

[0047] Talc 3, particle size D 50 8μm, manufacturer Liaoning Xinda, brand AH-1250N6;

[0048] Montmorillonite, particle size D 50 1.4μm, manufacturer BASF, brand Translink 445.

[0049] 5) Organic opening aids

[0050] Erucic acid amide, manufacturer: Croda, UK, brand name: Crodamide ER-CH-BE-(SI);

[0051] Oleic acid amide, manufacturer Crodamida, UK, brand name Crodamida VRX;

[0052] Monoglycoside ester, manufacturer Binzhou Jinsheng, brand ST-101;

[0053] N,N'-ethylenebisstearamide, manufacturer: Indonesia PT.CMS CHEMICAL, brand: EBS B50;

[0054] Feto wax, manufacturer Shell, brand SX-70;

[0055] Pentaerythritol stearate, manufacturer: Italy, brand: PETs;

[0056] Fatty acid amide, manufacturer Suzhou Xingtai Guoguang, brand TAS-2A;

[0057] Stearic acid, manufacturer: Sven, Indonesia, brand name SA-1801.

[0058] 2. Preparation method of biodegradable film material of the present invention

[0059] According to the formula, the components are mixed evenly and then added into a twin-screw extruder, melt-extruded and granulated at 160-200° C. to obtain a biodegradable film material; wherein the screw speed of the twin-screw extruder is 250-350 rpm.

[0060] Table 2 Weight parts of each component of the biodegradable film material in Examples 1 to 14

[0061]

[0062]

[0063] Table 3 Weight parts of each component of the biodegradable composite material in Examples 15 to 18 and Comparative Examples 1 to 11

[0064]

[0065]

[0066] 3. Performance testing

[0067] 1) High-speed film blowing capacity: Use domestic Zhenhao high-speed film blowing machine, control the film thickness to 25μm, the film circumference to 380mm, adjust the feeding speed, fan and traction speed to improve the film blowing capacity, and take the maximum capacity that can achieve stable film blowing (the film does not have breathing-like shaking or large swings) as the maximum capacity of high-speed film blowing.

[0068] 2) Opening level assessment

[0069] K1: Natural opening, just shake it gently to open all the bags;

[0070] K2: Rub the bag by hand to open it, and shake it vigorously to open all the bags;

[0071] K3: The accordion cannot be opened naturally and can be easily torn apart;

[0072] K4: The bag cannot be opened normally, but can be torn apart without deformation;

[0073] K5: The bag cannot be opened normally and is severely deformed after being torn open.

[0074] 3) Dyne value: tested with a dyne pen.

[0075] 4) Dart impact performance: tested using method A of the national standard GB / T 9639.1-2008.

[0076] Table 4 Performance of biodegradable film materials in various embodiments and comparative examples

[0077]

[0078]

[0079] According to the data in Table 3, the high-speed film blowing capacity of the biodegradable film materials in Examples 1 to 18 is ≥60kg / h, the opening grade is all K1, the dyne value is ≥30, and the dart impact is ≥200g, indicating that the biodegradable film material of the present invention is not only suitable for high-speed film blowing, but also has good opening performance, high dyne value and excellent dart impact performance. At the same time, according to Comparative Examples 1 and 2, it can be seen that if the molecular weight distribution coefficient of the PBAT resin is too small, the capacity of high-speed film blowing will be greatly reduced, and if the molecular weight distribution coefficient is too large, the dart impact performance of the biodegradable film will be significantly reduced; according to Comparative Examples 3 and 4, it can be found that if the T content in the PBAT resin is too high, the dart performance of the biodegradable film will be poor, and if the T content in the PBAT resin is too low, the opening performance of the biodegradable film will be poor. According to Comparative Examples 5 and 6, it can also be found that if the number average molecular weight of the PBAT resin is too small or too large, the high-speed film blowing capacity of the biodegradable film material will be reduced. In addition, according to Comparative Examples 7 to 9, it can be seen that when the D-lactic acid in the PLA resin is too high or the particle size of calcium carbonate is too small, the opening performance of the biodegradable film is poor, while when the particle size of calcium carbonate is too large, the dart impact performance of the biodegradable film is poor. According to Comparative Examples 10 and 11, it can be found that when the particle size of the inorganic opening agent is too small, the opening performance of the biodegradable film is easily greatly reduced, and when the particle size of the inorganic opening agent is too large, the dart impact performance of the biodegradable film is poor.

[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A biodegradable film material, characterized in that: By weight, it includes the following components: PBAT resin 39-85.6 parts, PLA resin 2-10 parts, calcium carbonate 10-40 parts, inorganic opening aid 2-10 parts, organic opening aid 0.2-1 part; The molar content of D-lactic acid in the PLA resin is ≤6%; The particle size D of the calcium carbonate 50 1.5~2.5μm; The particle size D of the inorganic opening agent 50 1~5μm.

2. The biodegradable film material according to claim 1, characterized in that: The biodegradable film material comprises 50 to 66.5 parts by weight of PBAT resin, 4 to 8 parts by weight of PLA resin, 25 to 35 parts by weight of calcium carbonate, and 4 to 6.5 parts by weight of an inorganic opening aid.

3. The biodegradable film material according to claim 1, characterized in that: Based on the total molar amount of the terephthalic acid monomer unit and the adipic acid monomer unit in the PBAT resin, the molar proportion of the terephthalic acid monomer unit is 46% to 50%; the number average molecular weight of the PBAT resin is 60,000 to 80,000 g / mol, and the molecular weight distribution coefficient is 1.6 to 1.

7.

4. The biodegradable film material according to claim 3, characterized in that: The number average molecular weight of the PBAT resin is 65,000 to 75,000 g / mol.

5. The biodegradable film material according to claim 3, characterized in that: The molecular weight distribution coefficient of the PBAT resin is 1.62 to 1.

68.

6. The biodegradable film material according to claim 1, characterized in that: The molar content of D-lactic acid in the PLA resin is 1% to 5%.

7. The biodegradable film material according to claim 1, characterized in that: The inorganic opening aid includes at least one of talc, montmorillonite and mica.

8. The biodegradable film material according to claim 1, characterized in that: The organic opening aid comprises at least one of erucamide, oleamide, monoglycoside ester, N,N'-ethylene bisstearamide, Fischer wax, pentaerythritol stearate, fatty acid amide and stearic acid.

9. The method for preparing the biodegradable film material according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing the components uniformly and then melting and extruding the components to obtain a biodegradable film material.

10. Use of the biodegradable film material according to any one of claims 1 to 8 in the preparation of biodegradable film bags.

Citation Information

Patent Citations

  • Biodegradable material and preparation method thereof

    CN115403902A

  • PLA (polylactic acid) modified material, preparation method thereof and PLA biodegradable mulching film

    CN103709695A

  • Completely-biodegradable blown film as well as preparation method and application of completely-biodegradable blown film

    CN109177401A

  • Environment-friendly tensile film and manufacturing process thereof

    CN110607054A

  • Talcum powder-filled full-biodegradable special film blowing material and preparation method thereof

    CN111484709A

Cited By

  • Biodegradable film material, and preparation method therefor and use thereof

    WO2026158000A1